Pengaruh Efikasi Diri Terhadap Kesiapan Kerja pada Mahasiswa Tingkat Akhir Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar - Ayu Liyan Pratiwi; Andi Mustika Amin; Uhud Darmawan Natsir; Romansyah Sahabuddin; Tenri Sayu Puspitaningsih Dipoatmodjo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to determine the influence of self-efficacy on work readiness in final year students of the Management Study Program at the Faculty of Economics and Business, Makassar State University. This research used quantitative methods involving 65 female students who were actively studying at the Management Study Program, Faculty of Economics and Business, Makassar State University class of 2020. Data was collected using a questionnaire in the form of a Likert scale. Data analysis in this research uses simple linear regression with the help of a program microsoft excel 2007 and program software SPSS statistics 20. The results of this study show that self-efficacy positively and significantly influences work readiness in final year students of the Management Study Program at Makassar State University.